Answer:
The answer to your question is: g(3) = 34
Step-by-step explanation:
Function g(x) = 4(x)² - 3(x) + 7
g(3) = 4(3)² - 3(3) + 7 substitution
g(3) = 4(9) - 3(3) + 7 simplify
g(3) = 36 - 9 + 7
g(3) = 36 - 2
g(3) = 34
Answer:
Step-by-step explanation:
Zero property because you are using zeros to multiply
To find the magnitude of a vector, take the components, square them, then add them, then take the square root. This is very similar to the Pythagorean Theorem.
For your particular problem, I’ve included a picture showing how that specific calculation is done. :)
Hello,
ln(y)=ln(x^(ln(x))=ln(x)*ln(x)=(ln(x))²
(ln(y))'=2ln(x)*1/x
(1/y)*y'=2ln(x) / x
y'=(2 ln(x) * x^(ln(x)) ) /x
Huh??? Where is the question?